The Relationship between Activeness, the Role of Cadres and Family Support with Mothers' Compliance in Bringing Toddlers to Posyandu - Ningtyas, Dwi Harnanik Yudhyas Suci; Kurniawan, Ardhiles Wahyu; Hastuti, Apriyani Puji (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Integrated Health Service (Posyandu) has a strategic role in maintaining toddler health through growth and development monitoring, immunization, and nutrition education. The level of maternal compliance in bringing toddlers remains a challenge due to the influence of both internal and external factors. Objective This study aims to analyse the relationship between activeness, the role of cadres, and family support with maternal compliance in bringing children under five years Method This study uses correlational study with cross- sectional. Data were collected through a questionnaire covering independent variables (activeness, role of cadres, family support) and dependent variables (compliance). The population was all toddlers registered at the Integrated Health Service Seruni BTN Graha Pasir Ona Rangkasbitung, Banten in 2025, totalling 69 toddlers. Technique sampling used accidental sampling so that the entire population became respondents. Inclusion criteria included mothers who have children under- five years and recorded until July 2025. Data analysis was performed using the Chi-Square test with p < 0.05. Results The results of the study showed that there was a significant relationship between maternal activity (p-value= 0.001), the role of cadres (p-value= 0.004), and family support (p-value= 0.002) with maternal compliance in bringing toddlers to the integrated health service. Conclusion In conclusion, maternal compliance is influenced by a combination of active participation, cadre support, and family involvement. Optimizing the role of cadres and strengthening family support are crucial for increasing maternal participation in integrated healthcare activities.